Dendropaemon Perty, 1830: taxonomy, systematics and phylogeny of the morphologically most derived phanaeine genus (Coleoptera: Scarabaeidae, Scarabaeinae, Phanaeini) - Génier, François; Arnaud, Patrick (Zootaxa, 2016)
The taxonomy and systematics of the Neotropical genus Dendropaemon Perty is revised. The current study recognize 41 species organized into 12 subgenera. The establishment of the subgenera is reflecting the presented phylogenetic analysis. Six subgenera are established from previously available genus group names: Coprophanaeoides Edmonds, 1972; Dendropaemon Perty, 1830; Enicotarsus Laporte, 1831; Eurypodea Klages, 1906; Onthoecus Lacordaire, 1856; Paradendropaemon Edmonds, 1972 and Tetramereia Klages, 1907. Six additional subgenera are described as new: Glaphyropaemon n. subg.; Nigropaemon n. subg.; Rutilopaemon n. subg.; Streblopaemon n. subg.; Sulcopaemon n. subg. and Titthopaemon n. subg. The following 18 species are described as new: Dendropaemon (Coprophanaeoides) bluti n. sp.; Dendropaemon (Coprophanaeoides) carinifer n. sp.; Dendropaemon (Coprophanaeoides) compressipennis n. sp.; Dendropaemon (Coprophanaeoides) cribrosus n. sp.; Dendropaemon (Coprophanaeoides) furtadoi n. sp.; Dendropaemon (Coprophanaeoides) inflatus n. sp.; Dendropaemon (Coprophanaeoides) pilosissimus n. sp.; Dendropaemon (Dendropaemon) aenigmaticus n. sp.; Dendropaemon (Dendropaemon) amazonicus n. sp.; Dendropaemon (Dendropaemon) angustulus n. sp.; Dendropaemon (Dendropaemon) flechtmanni n. sp.; Dendropaemon (Dendropaemon) larseni n. sp.; Dendropaemon (Glaphyropaemon) inemarginatus n. sp.; Dendropaemon (Nigropaemon) nigritulus n. sp.; Dendropaemon (Onthoecus) lydiae n. sp.; Dendropaemon (Onthoecus) morettoi n. sp.; Dendropaemon (Paradendropaemon) vazdemelloi n. sp.; Dendropaemon (Sulcopaemon) latistriatus n. sp.. The following nomen novum: Dendropaemon (Onthoecus) attalus nom. nov. is created to replace the primary junior homonym Dendropaemon amyntas Harold, 1868. Except for Dendropaemon montei Pessôa & Lane, 1936, type material of all the species have been examined and lectotypes designated for the following two species: Dendropaemon fasces Blut, 1939 and Dendropaemon lobatus Waterhouse, 1891. In order to stabilize nomenclature, neotypes were also designated for the following species: Dendropaemon convexus Harold, 1869; Enicotarsus ater Laporte, 1832; Enicotarsus quadratus Laporte, 1932 and; Enicotarsus viridipennis Laporte, 1831. Color habitus are presented for each of the valid species.